Romania : First Review Under the Stand-By Arrangement, Request for Waiver of Nonobservance of Performance Criterion, and Request for Modification and Establishment of Performance Criteria; Statement by the IMF Staff Representative; and Press Release on the Executive Board Discussion;. (IMF Staff Country Reports; Country Report ;, 2009)
The contraction in Romania's domestic demand has set off a sharp correction in external imbalances and helped ease pressures on inflation. Real GDP contracted by 7.6 percent in the first half of 2009, compared with 2 percent projected under the program, on account of a sharp drop in domestic demand, especially consumption. This posed a particular challenge for public finances, where weakening revenues required sharp temporary cuts in spending to meet what turned out to be structurally tight targets. Monetary and exchange rate policies will remain anchored on targeting inflation over the medium term.